Aegean Greece in the fourth century BC - Buckler, John. (Brill's Companions in Classical Studies Online I, ISBN: 9789004219274., 2003)
This book covers the political, diplomatic, and military history of the Aegean Greeks of the fourth century BC, raising new questions and delving into old disputes and controversies. It includes their power struggles, the Persian involvement in their affairs, and the ultimate Macedonian triumph over Greece. It deals with the political concept of federalism and its relations to the ideal of the polis. The volume concludes with the triumph of Macedonian monarchy over the polis. In dealing with the great public issues of fourth-century Greece, the approach to them includes a combination of sources. The usual literary and archaeological information forms the essential foundation for the topographical examination of every major site mentioned in the text. Numismatic evidence likewise finds its place here.